Delivery after Operation for Deeply Infiltrating Endometriosis. (19th July 2016) - Allerstorfer, Christina; Oppelt, Peter; Enzelsberger, Simon H.; Shamiyeh, Andreas; Schimetta, Wolfgang; Shebl, Omar Josef; Mayer, Richard Bernhard
Abstract : Background. It has been suggested that, during pregnancy, endometriosis can cause a variety of disease-related complications. Objectives. The purpose of the study was to find out if women with histologically confirmed endometriosis do have a higher risk of adverse pregnancy outcome and if they suffer from a higher rate of complications during labor. Study Design. 51 women who underwent surgery because of deeply infiltrating endometriosis in the General Hospital Linz and the Women's General Hospital Linz and who gave birth in the Women's General Hospital Linz after the surgery were included in our survey. Results. 31 women (60.8%) had a spontaneous delivery and in 20 women (39.2%) a caesarean section was performed. There were no cases of third- and fourth-degree perineal lacerations. Collectively there were 4 cases (7.8%) of preterm delivery and one case (2.0%) of premature rupture of membranes. In two women (6.5%) a retained placenta was diagnosed. Conclusions. Our study is the first description on delivery modes after surgery for deeply infiltrating endometriosis. We did not find an elevated risk for perineal or vaginal laceration in women with a history of surgery for deeply infiltrating endometriosis, even when a resection of the rectum or of the posterior vaginal wall had been performed.